SPIRITUALITY'S ROLE IN WEAKENING INTENTIONS FOR ACCOUNTING FRAUD - Siska, Siska; Zulhelmy, Zulhelmy; Hidayat, Rizki; Yusniawati, Erni (JRAK, 2024)
Financial fraud in zakat institutions has the potential to erode public trust in zakat payment. The research aims at examining the role of spirituality in moderating the elements that affected accounting fraud intention. The method used was a quantitative research with 170 respondents with a focus on Zakat management entities in Riau Province. The research’s data analysis method used the Moderated Structural Equation Model (MSEM). The findings of this research suggested that spirituality could reduce the impact of opportunity on accounting fraud intention. However, spirituality could not reduce the impact of rationalization and ego on accounting fraud intention. This had implications for organizations to pay more attention to psychological components, particularly spirituality, to minimize accounting fraud.